2015
DOI: 10.1039/c5cp00309a
|View full text |Cite
|
Sign up to set email alerts
|

Design of PAMAM-COO dendron-grafted surfaces to promote Pb(ii) ion adsorption

Abstract: An expanding area of green technology is the wastewater treatment of heavy metal ions. As the adsorption of cations onto solid surfaces has been proven to be successful, recent research has demonstrated enhanced adsorption profiles by grafting dendron brushes onto a solid support. Via the molecular dynamics technique, we examine the adsorption of Pb(II) ions onto polyamidoamine (PAMAM) with carboxylate terminal groups through a coarse-grained implicit solvent model. We identify dendron generations and grafting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…Various modifications were reported to enhance the applicability of dendrimers as efficient sorbents [5]. Dendrimers were tethered to silica gel, mesoporous silica (SBA-15), natural clay, fiber, graphene oxide, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various modifications were reported to enhance the applicability of dendrimers as efficient sorbents [5]. Dendrimers were tethered to silica gel, mesoporous silica (SBA-15), natural clay, fiber, graphene oxide, etc.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier work demonstrated and characterized the adsorption behavior of surface‐grafted PAMAM dendrons with carboxylate groups on its terminal ends by calculating distributions and averages of the coordination with ions . In this current study, the maximum cutoff for defining coordination is 0.5811 nm or 0.47(2(2 1/6 −1)+1).…”
Section: Resultsmentioning
confidence: 71%
“…Nowadays, many kinds of inorganic nanomaterials are being widely reported that can be directly used for versatile research. [29][30][31][32][33][34][35][36] Dendritic structures combined with metal nanoparticles (MNPs) have been suggested for rapid, easy, and economical separation of target molecules from large volumes of toxic waste. As most common adsorbents, polymer microspheres, metal oxides, mesoporous nanostructures, and activated carbons have been synthesized to study their adsorption properties due to their large surface area and high adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Recently, dendrimers have been considered as effective agents for wastewater treatment and environmental pollution control because of their high binding affinity to metal ions and organic dyes. [29][30][31][32][33][34][35][36] Dendritic structures combined with metal nanoparticles (MNPs) have been suggested for rapid, easy, and economical separation of target molecules from large volumes of toxic waste. [28,37,38] In the present study, we have successfully synthesized polyhydroxy dendrimer-modified magnetic nanoparticles (Fe 3 O 4 @SiO 2 -TRIS) using tris(hydroxymethyl) aminomethane (TRIS) as biocompatible precursor and evaluated their efficiency for the removal of two anionic dyes, namely Acid Red 114 (AR-114) and Reactive Black 5 (RB-5), from aqueous solutions.…”
mentioning
confidence: 99%